THE INTERACTION OF CIVIL SOCIETY AND THE STATE - R. V. Fyodorof; L. A. Pafomova (Дискурс, 2016)
The article analyzes theoretical statements concerning interaction of state and civil society, which were formed in the European philosophy of the XVII-XIX centuries (D. Locke, G. Hegel, K. Marx). On the basis of the comparative analysis the generalized concept of civil society is formulated. The specific interaction mechanisms of institutions of the modern Russian state and their impact on the formation and development of civil society are discussed.